2012
DOI: 10.1111/j.1600-0897.2012.01123.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms and Recurrent Spontaneous Abortions: An Overview of Current Knowledge

Abstract: CitationDaher S, Mattar R, Gueuvoghlanian-Silva BY, Torloni MR. Genetic polymorphisms and recurrent spontaneous abortions: an overview of current knowledge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 73 publications
1
60
0
2
Order By: Relevance
“…Our results demonstrated that RM patients had a significantly lower frequency of the G allele of rs1799983, which is consistent with previous studies in Koreans (Shin et al, 2010), whites (Hefler et al, 2002), and Indians (Parveen et al, 2011). By contrast, some studies have not confirmed this association (Daher et al, 2012).…”
Section: Discussionsupporting
confidence: 83%
“…Our results demonstrated that RM patients had a significantly lower frequency of the G allele of rs1799983, which is consistent with previous studies in Koreans (Shin et al, 2010), whites (Hefler et al, 2002), and Indians (Parveen et al, 2011). By contrast, some studies have not confirmed this association (Daher et al, 2012).…”
Section: Discussionsupporting
confidence: 83%
“…Dysregulated immunity was proposed as a potential mechanism underlying RPL 3,24 and that interindividual variation in the anti-inflammatory and proinflammatory cytokine levels may modify the risk of unexplained RPL. 7,25 In this regard, the success of pregnancy depends on maintaining a fine balance between Th1 and Th2 immunity. 26 This was reportedly characterized by a shift to Th2 (humoral) immunity, which involves augmentation in the production of Th2 cytokines accompanied by attenuation of Th1 cytokines synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been carried out to evaluate the relationship between cytokines, angiogenic mediators, and hormones gene polymorphisms and unexplained recurrent spontaneous abortion. The results of these studies are mostly contradictory, and few significant associations have been identified (1). Up to present time, the evidence is insufficient to support the evaluation of cytokines, angiogenic mediators, and hormones gene polymorphism in routine workup in all cases of recurrent pregnancy loss, and many of these genetic tests have not yet implemented the major obstetric guidelines.…”
Section: E] Cytokines Genes Factor (Insert Ref (7)mentioning
confidence: 93%